2021
DOI: 10.1007/s10565-021-09582-4
|View full text |Cite
|
Sign up to set email alerts
|

ZNF471 modulates EMT and functions as methylation regulated tumor suppressor with diagnostic and prognostic significance in cervical cancer

Abstract: Cervical cancer (CC) is a leading cause of cancer-related death among women in developing countries. However, the underlying mechanisms and molecular targets for therapy remain to be fully understood. We investigated the epigenetic regulation, biological functions, and clinical utility of zinc-finger protein 471 (ZNF471) in CC. Analysis of cervical tissues and five independent public datasets of CC showed significant hypermethylation of the ZNF471 gene promoter. In CC cell lines, promoter DNA methylation was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…ZNF281 has been proved to play a crucial role in controlling cellular stemness expression and EMT by EMT induction and regulation of EMT-associated gene expression in colorectal cancer [30]. ZNF471 suppressed cervical cancer cell invasion through modulating EMT by negatively regulating Wnt/ β-catenin signaling pathway [31]. In our study, we observed that ZNF677 signi cantly reduced 786-0 cell invasion.…”
Section: Discussionsupporting
confidence: 58%
“…ZNF281 has been proved to play a crucial role in controlling cellular stemness expression and EMT by EMT induction and regulation of EMT-associated gene expression in colorectal cancer [30]. ZNF471 suppressed cervical cancer cell invasion through modulating EMT by negatively regulating Wnt/ β-catenin signaling pathway [31]. In our study, we observed that ZNF677 signi cantly reduced 786-0 cell invasion.…”
Section: Discussionsupporting
confidence: 58%
“…Zinc finger proteins play crucial roles in transcriptional and post-transcriptional regulation of immune response [ 45 ] and are involved in cancer development and progression [ 46 ]. Among the identified zinc finger proteins in our study, ZNF471 functions as a tumor suppressor in several cancers and is frequently hypermethylated in tumor tissues [ 47 , 48 , 49 , 50 , 51 ]. Higher levels of ZNF577 methylation in leukocytes have been associated with obesity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further example includes ZNF471, which acts as a tumor suppressor in cervical cancer. Hypermethylation of the ZNF471 gene promoter and low ZNF471 expression was correlated with poor overall and recurrence-free survival in cervical cancer (Bhat et al, 2021).…”
Section: Introductionmentioning
confidence: 95%